An adaptive multispectral mechano-optical system for multipurpose applications - Liang, Leilei (2023)
Mechano-optical systems with on-demand adaptability and a broad spectrum from the visible to microwave are critical for complex multiband electromagnetic (EM) applications. Most existing material systems merely have dynamic optical or microwave tunability because their EM wave response is strongly wavelength-dependent. Inspired by cephalopod skin, we develop an adaptive multispectral mechano-optical system based on bilayer acrylic dielectric elastomer (ADE)/silver nanowire (AgNW) films, which reconfigures the surface morphology between wrinkles and cracks via mechanical contraction and stretching. Such morphological evolution regulates the direct transmission/reflection and scattering behavior of visible-infrared light and simultaneously alters the conductive network in a AgNW film to influence its microwave characteristics. The designed system features switching between visible-infrared-microwave transparency and opacity, continuous regulation, wide spectral window (0.38-15.5 μm and 24,200-36,600 μm), excellent recyclability (500 times), and rapid response time (<1 s). These grant the system great potential as platforms for various promising applications such as smart windows, switchable EM devices, dynamic thermal management, adaptive visual stealth, and human motion detection.